Small-Molecule Inhibitors Overcome Epigenetic Reprogramming for Cancer Therapy - Wenjing Xiao; Wenjing Xiao; Qiaodan Zhou; Xudong Wen; Rui Wang; Ruijie Liu; Tingting Wang; Jianyou Shi; Yonghe Hu; Yonghe Hu; Jun Hou; Jun Hou (Frontiers Media S.A., 2021)
Cancer treatment is a significant challenge for the global health system, although various pharmacological and therapeutic discoveries have been made. It has been widely established that cancer is associated with epigenetic modification, which is reversible and becomes an attractive target for drug development. Adding chemical groups to the DNA backbone and modifying histone proteins impart distinct characteristics on chromatin architecture. This process is mediated by various enzymes modifying chromatin structures to achieve the diversity of epigenetic space and the intricacy in gene expression files. After decades of effort, epigenetic modification has represented the hallmarks of different cancer types, and the enzymes involved in this process have provided novel targets for antitumor therapy development. Epigenetic drugs show significant effects on both preclinical and clinical studies in which the target development and research offer a promising direction for cancer therapy. Here, we summarize the different types of epigenetic enzymes which target corresponding protein domains, emphasize DNA methylation, histone modifications, and microRNA-mediated cooperation with epigenetic modification, and highlight recent achievements in developing targets for epigenetic inhibitor therapy. This article reviews current anticancer small-molecule inhibitors targeting epigenetic modified enzymes and displays their performances in different stages of clinical trials. Future studies are further needed to address their off-target effects and cytotoxicity to improve their clinical translation.